CYTOTOXICITY EFFECT OF IONIC LIQUID-GRAVIOLA FRUIT (ANNONA MURICATA) EXTRACT TO HUMAN COLON CANCER (HT29) CELL LINES - Daddiouaissa, Djabir; Amid, Azura; AHMED KABBASHI, NASSERELDEEN; ADAM MOHAMMED ELNOUR, AHMED; ADIKA KHAIRY BIN MOHD SHAIFUDIN EPANDY, MOHAMAD (IIUM Engineering Journal, 2021)
The present study aimed to investigate the anti-proliferative effect of the ionic liquid-Graviola fruit (IL-GFE) extract on colon adenocarcinoma (HT29) cell lines and their kinetics behaviour to assess the Graviola fruit potential as a therapeutic alternative in cancer treatment. The phytoconstituents content of IL-GFE was identified using GC-TOFMS apparatus and measured its cytotoxicity on HT29 by tetrazolium bromide. Then the cytokinetic behaviour of the treated HT29 cells with IL-GFE was illustrated using the cells' growth curve. Besides, the cell cycle phase perturbation for the treated HT29 was applied using a flow cytometry technique. Qualitative identification of phytoconstituents of IL-GFE showed that Graviola fruit contains acetogenins, alkaloids, flavonoids, tannins and saponins compounds. IL-GF extract displayed a cytotoxicity effect on HT29 cells with the IC50 value of 10.56 µg/mL, while Taxol showed an IC50 value of 1.22 µg/mL. IL-GFE also decreased the cell generation number from 3.93 to 2.96 generations compared to Taxol-treated cells 2.01 generations. The microscope observation of the HT29 cells treated with the crude IL-GFE displayed loss of density and cell detachment. The extract's growth inhibition was related to the cell cycle arrest at the G0/G1 phase. IL-GFE inhibited colon adenocarcinoma HT29 cells' proliferation and affected their kinetic behaviour by lowering cell viability, inducing apoptosis, and arresting the cell cycle at the G0/G1 phase. ABSTRAK: Kajian ini bertujuan untuk mengkaji kesan anti-proliferatif ekstrak buah-ion Graviola (IL-GFE) pada garis sel adenokarsinoma kolon (HT29) dan tingkah laku kinetik mereka untuk menilai potensi buah Graviola sebagai alternatif terapi untuk barah rawatan. Kandungan fitokonstituen IL-GFE dikenal pasti menggunakan alat GC-TOFMS dan mengukur sitotoksisitasnya pada HT29 oleh tetrazolium bromida. Kemudian tingkah laku sitokinetik sel HT29 yang dirawat dengan IL-GFE digambarkan menggunakan keluk pertumbuhan sel. Selain itu, gangguan fasa kitaran sel untuk HT29 yang dirawat diaplikasikan menggunakan teknik sitometri aliran. Pengenalpastian kualitatif fitokonstituen IL-GFE menunjukkan bahawa buah Graviola mengandungi asetogenin, alkaloid, flavonoid, tanin dan sebatian saponin. Ekstrak IL-GF memperlihatkan kesan sitotoksisiti pada sel HT29 dengan nilai IC50 10.56 µg/mL, sementara Taxol menunjukkan nilai IC50 1.22 µg/mL. IL-GFE juga menurunkan jumlah penjanaan sel dari 3.93 hingga 2.96 generasi berbanding sel yang dirawat Taxol 2.01 generasi. Pemerhatian mikroskop sel HT29 yang dirawat dengan IL-GFE kasar menunjukkan kehilangan ketumpatan dan detasmen sel. Perencatan pertumbuhan ekstrak berkaitan dengan penangkapan kitaran sel pada fasa G0/G1. IL-GFE menghalang percambahan sel HT29 adenokarsinoma kolon dan mempengaruhi tingkah laku kinetik mereka dengan menurunkan daya maju sel, mendorong apoptosis, dan menghentikan kitaran sel pada fasa G0/G1.